Understanding and effectively addressing disparities in obesity: A systematic review of the psychological determinants of emotional eating behaviours among Black women. (17th February 2020) - Pickett, Stephanie; Burchenal, Clare A.; Haber, Leora; Batten, Kendra; Phillips, Erica
Summary: Emotional eating may be a particularly important contributor to differences in body weight and weight loss response to behavioural interventions among non‐Hispanic Black women. We performed a systematic review on the impact of psychological factors (stress, anxiety, depression, and discrimination) upon emotional eating and weight among non‐Hispanic Black women, applying the Preferred Reporting Items for Systematic Reviews and Meta‐analysis for relevant studies. The initial search yielded 4593 articles with 15 accepted for review. Based on this review, there is a suggestion that negative emotions, in particular, perceived stress, may be predictive of emotional eating among non‐Hispanic Black women. Results from the only two longitudinal studies identified by the review indicate that stress influences emotional eating, and emotional eating predicts weight gain over time. Findings from this review highlight the need for more studies that examine various negative emotions that may lead to emotional eating and weight gain among non‐Hispanic Black women. Findings from this review also highlight the need for more rigorous studies to differentiate the effects of emotional eating from that of the physiologic (ie, activation of the hypothalamic‐pituitary axis) responses to stress and its impact on high‐risk groups.